Household Resilience in Rural and Urban Societies: A Sociological-Anthropological Perspective - Rozikin, Opik; Sunaryo Mukhlas, Oyo; Ahmad Saebani, Beni (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2024)
This paper examines the sociological and anthropological perspectives on household resilience in rural and urban communities. This research is grounded in significant social change, where values and social structure shifts impact how individuals and families sustain their existence. This study aims to understand how sociocultural factors influence household resilience strategies and compare the differences and similarities between rural and urban communities in this context. The methods used include literature studies. The theoretical framework for this research encompasses social structure theory, social network theory, and anthropological approaches that emphasize an in-depth understanding of cultural practices. The discussion results indicate that rural communities rely on community solidarity and tradition in building household resilience, whereas urban communities prioritize individualistic social networks. The implications of this research provide insights for policymakers and social practitioners in designing more effective intervention programs to enhance household resilience, considering each community's unique characteristics. This study is expected to contribute to the further development of research in the fields of sociology and anthropology, as well as offer a new perspective on understanding social dynamics in Indonesia.